Effect from usage and autoclave sterilization on torsional fracture resistance of heat-treated nickel-titanium instruments: an in-vitro study - Kang, Yoo Jung; Alshehhi, Aisha; Al Raeesi, Dana; Alkhatib, Zuhair; Jamal, Mohamed; El Abed, Rashid; Kim, Hyeon-Cheol (Frontiers in Materials, 2023)
This study aimed to evaluate the effect from usage and autoclaving on torsional fracture resistance of heat-treated nickel-titanium rotary instruments. ProTaper Gold F2 (PG) and TruNatomy Prime (TN) were selected. For group-N, new files were tested to make a baseline torsional resistance. For group-U, files underwent instrumentation in a J-shaped canal block, and files were tested. For group-S, files underwent instrumentation as in the group-U and followed by autoclave sterilization then were tested. Maximum torsional strength and distortion angel until fracture were measured using a customized device and toughness was calculated. Statistical analysis was conducted at the significance level of 95%. The topographic appearances of torsional fracture fragments were examined under scanning electron microscopy. PG showed significantly higher torsional strength after usage and sterilization; however, TN had reduced torsional strength (p < 0.05). PG showed significantly higher torsional strength in group-S than subgroup-N, while TN showed significantly lower torsional strength in group-U than group-N (p < 0.05). Regardless of the test conditions, PG showed significantly higher torsional strength and toughness than TN while TN had bigger distortion angle than PG (p < 0.05). The mechanical loads from usage and heat application during sterilization may result in alteration of torsional resistances according to geometry and alloy characteristics.